2016
DOI: 10.1007/s40279-016-0559-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of Exercise Interventions to Improve Postural Control in Older Adults: A Systematic Review and Meta-Analyses of Centre of Pressure Measurements

Abstract: BackgroundPrevious reviews have shown balance in older adults to be improved with exercise. However, it is currently unclear whether postural control, indicated by centre of pressure (COP) measurement, can be improved in older adults and thus whether postural control could be a mechanism to improve balance.ObjectivesThe purpose of this systematic review was to assess the effectiveness of force platform COP variables to identify changes in postural control following exercise interventions in older adults. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 45 publications
5
90
0
7
Order By: Relevance
“…[5][6][7][8][9]21,22 Fortunately, once identified, postural sway deficits can be treated by using exercise-based training interventions. 29 To this extent, it is worth noting that a recent study showed that BBT (i.e. postural sway) reductions were possible for older adults using a 90-day resistance training intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9]21,22 Fortunately, once identified, postural sway deficits can be treated by using exercise-based training interventions. 29 To this extent, it is worth noting that a recent study showed that BBT (i.e. postural sway) reductions were possible for older adults using a 90-day resistance training intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Such abnormalities have previously been associated with a number of poor clinical outcomes including, importantly, increased fall risk . Fortunately, once identified, postural sway deficits can be treated by using exercise‐based training interventions . To this extent, it is worth noting that a recent study showed that BBT (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They can focus, for example, on balance or muscle strength exercises, virtual reality and active game exercises (i.e. Wii Fit balance game training, exergames), whole‐body vibration platform exercises, hippotherapy exercises, tai chi chuan or qigong exercises, or combinations of several exercises . If the balance data were not available in the article or after sending a request to the author, the study was excluded from the meta‐analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion is in accordance with results observed in the literature in other populations. [15][16][17][18] Indeed, types of exercise inducing greater increases of postural stability in older persons [15][16][17] or in children with cerebral palsy are those specifically targeting balance abilities. 18 Moreover, standing balance measured by stabilometry in children with cerebral palsy was not improved after a strength exercise intervention (resisted ankle and knee exercise).…”
Section: Effects Of Exercise Interventions and Subgroup Analyses Statmentioning
confidence: 99%
“…ML postural sway is associated more with fall risks in older people compared to AL postural sway [110]. The effect of exercise on postural control becomes more apparent when the balance task is performed without vision [111]. When the eyes are closed, balance relies solely on efferent neuromuscular and sensorimotor input [112], which can be improved with exercise [113].…”
Section: Postural Controlmentioning
confidence: 99%